Sistem Pendukung Keputusan Diagnosa Penyakit Tanaman Cabai Merah Menggunakan Metode TOPSIS Berbasis Web di Desa Kerik Magetan Jawa Timur - Pebri Romadhon; Tomi Tristono; Pradityo Utomo (APTIKOM SUMSEL, 2021)
Kerik Village, Takeran District, Magetan Regency, part of the community, work as red chilli farmers. Farmers experience some difficulties in red chilli cultivation because farmers still have little experience in red chilli cultivation. The farmers cannot know the types of diseases and pests and the symptoms that hit chilli plants that can reduce the productivity of chilli plants and can even cause crop failure. In addition, farmers also do not have experience handling it when they encounter problems that hit chilli plants that are being cultivated. To assist farmers in overcoming these problems, a web-based decision support system was built using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The decision support system was created and designed using the Waterfall method and tested using the Blackbox Testing system testing method. With this decision support system, it is hoped that it will help farmers in Kerik Village diagnose diseases of the red chilli plants they cultivate. The test results from the Decision Support System for Diagnosing Red Chili Plant Diseases Using the Web-Based TOPSIS Method got the results as expected with the Blackbox Testing test, which brought the results of the percentage of system success of 100%.